Significant mechanical softening of copper under coupled electric and magnetic stimuli. (1st July 2023) - Yang, Yueqing; Wang, Yuecun; Lu, Huanhuan; Wang, Zhangjie; Xie, Degang; Zhao, Yongfeng; Du, Junli; Wang, Chaohua; Ma, En; Shan, Zhiwei
Abstract: The mechanical reliability of metallic components is vital for the stable operation of electrical equipment, especially for those used in ultra-high voltage transmission and electromagnetic launching, where metallic materials inevitably suffer from high-density current and strong magnetic field. However, little has been known about the mechanical behavior of metals under the electric-magnetic coupling stimuli. Here, by performing quantitative electromechanical tests under the built-in magnetic field inside transmission electron microscope, we found that copper, one of most commonly used conductive metals, can be significantly softened by the coupled electrical-magnetic stimuli, manifested as notable yield strength drop by five-times and obvious creep deformation at room temperature. A plausible mechanism behind the unusual softening, local-Lorentz-force-assisted dislocations depinning, has been proposed. Our results shed new light on understanding the deformation-induced failure of metals served in electromagnetic environments, and also inspire a new mechanical processing way for reshaping metals at much lower loads and temperatures. Graphical abstract: Image, graphical abstract